PENGARUH PENGGUNAAN MEDIA PETA TERHADAP KEMAMPUAN BERPIKIR SPASIAL SISWA KELAS XI SMAN 14 PADANG PADA MATERI PERSEBARAN WILAYAH RAWAN BENCANA ALAM DI INDONESIA - Andhani Putri Afriana; Ahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to determine whether the use of map media can affect the spatial thinking skills of students at SMAN 14 Padang City and to determine the learning outcomes of students' spatial thinking skills at SMAN 14 Padang City on the material of the distribution of areas prone to natural disasters in Indonesia using map media. This study used an experimental method with a quantitative research type and a sampling technique using the purposive sampling method by determining class XI F11 as the experimental class and class X F10 as the control class. The data collection techniques used were observation, tests, and documentation. The spatial thinking ability test was given after treatment to both classes. The test was given in the form of essay questions using spatial thinking indicators. The results showed that the average value of the essay test results of the experimental class students was higher than the control class. The average for the experimental class was 85.24 and the control class was 71.37. Based on the results of the independent sample t-test, it is also known that the significance value is 0.001 where the value is smaller than 0.05 so that H0 is rejected and Ha is accepted and it can be concluded that the use of map learning media has a positive impact on student learning outcomes on the material on the distribution of areas prone to natural disasters in Indonesia.